The national credit act: Interim attachment of goods sold on credit in a new era of South African consumer credit law - Smith, ML (Centre for Law and Society, 2026)
The financial crisis of 2007 has been described, by leading economists, as the worst financial crisis since the Great Depression of 1929.1 This crisis has contributed to the failure of businesses, the closure of banking and other financial institutions, and a dramatic decline in consumer wealth. The prevailing economic climate has created a proliferation of 'cash-strapped' consumers. The consumer, worldwide, has been left in a very poor state indeed, with many losing their jobs, their homes and their livelihoods. Unable to generate an income the consumer has turned to credit providers, often relying on the credit they provide to live. But, as countries fall deeper into recession consumers become worse off and are defaulting on their credit obligations.